Public Speaking of Regional Children's Forum (FAD) in West Java Province - Rinawati, Rini; Darmawan, Ferry; Fardiah, Dedeh; Subur Drajat, M. (KnE Social Sciences, 2023)
The research was conducted because the West Java Province DP3AKB formed the West Java Regional Children’s Forum (FAD) on September 24, 2004 for public to involve in providing socialization of children protection from violence. FAD is a representative of various schools in West Java. FAD has a role and function, namely as a pioneer and reporter regarding children’s issues. The effectiveness of communication is the key to the success of FAD management in carrying out their duties as pioneers and reporters. This is because the FAD management always deals with or interacts with many people. Public speaking knowledge and skills are the basis for the success of efforts to deliver messages about preventing violence against children. This study aims to see the knowledge and skills possessed by West Java FAD administrators. The research method used is a descriptive method with a qualitative approach. The research informants comprised 36 West Java FAD administrators who were representatives of all high school-levels throughout West Java. Through the questionnaires and interviews conducted, it was obtained that the FAD administrators already had sufficient knowledge about public speaking. In addition, public speaking skills are also owned by the West Java FAD management. Keywords: children’s forum, public speaking, communication